2015
DOI: 10.1016/j.bbi.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of TGF-β1 and TGF-β3 as regulators of encephalitogenic Th17 cells: Implications for multiple sclerosis

Abstract: The phenotype of the CD4+ T cells that mediate the CNS pathology in multiple sclerosis is still unclear, and yet a vital question for developing therapies. One of the conundrums is the role of TGF-β in the development of encephalitogenic Th17 cells. In the present study, TGF-β1 and TGF-β3 were directly compared in their capacity to promote the differentiation of myelin-specific Th17 cells that could induce experimental autoimmune encephalomyelitis (EAE). Myelin-specific CD4+ T cell receptor transgenic cells di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 38 publications
2
27
0
1
Order By: Relevance
“…Although TGF-β plus IL-6 drove Th17 differentiation efficiently in vitro, these cells failed to transfer EAE. We and others have shown that myelin-reactive Th17 generated with IL-6 in the absence of Th1/Th2 differentiation cytokines are highly encephalitogenic (32)(33)(34)(35). These data further confirmed that signaling components of the Th17 differentiation pathway determined the encephalitogenicity of Th17 cells but not IL-17 production itself.…”
Section: Introductionsupporting
confidence: 75%
“…Although TGF-β plus IL-6 drove Th17 differentiation efficiently in vitro, these cells failed to transfer EAE. We and others have shown that myelin-reactive Th17 generated with IL-6 in the absence of Th1/Th2 differentiation cytokines are highly encephalitogenic (32)(33)(34)(35). These data further confirmed that signaling components of the Th17 differentiation pathway determined the encephalitogenicity of Th17 cells but not IL-17 production itself.…”
Section: Introductionsupporting
confidence: 75%
“…However, in the case of encephalitogenic T cells, we and others have found that myelin-specific Th17 cells differentiated with IL-6 and TGFb are not encephalitogenic (Yang et al, 2009;Ghoreschi et al, 2010;Lee et al, 2015). In fact, TGFb is a negative regulator of T-bet, a key transcription factor in encephalitogenic T cells, irrespective of whether it has a Th1 or Th17 phenotype (Gocke et al, 2007;Yang et al, 2009;Lee et al, 2015). Thus, suppression of the TGFb pathway enhances T-bet expression, as well as promotes the differentiation of pathogenic Th17 cells, suggesting that miRNAs that suppress TGFb signalling may promote the development of autoreactive effector T cells.…”
Section: Discussionmentioning
confidence: 74%
“…TGFb has been shown to promote the development of Th17 cells in the presence of IL-6 in mice (Bettelli et al, 2006;Mangan et al, 2006;Veldhoen et al, 2006), suggesting that diminished TGFb signalling may negatively modulate Th17 cells. However, in the case of encephalitogenic T cells, we and others have found that myelin-specific Th17 cells differentiated with IL-6 and TGFb are not encephalitogenic (Yang et al, 2009;Ghoreschi et al, 2010;Lee et al, 2015). In fact, TGFb is a negative regulator of T-bet, a key transcription factor in encephalitogenic T cells, irrespective of whether it has a Th1 or Th17 phenotype (Gocke et al, 2007;Yang et al, 2009;Lee et al, 2015).…”
Section: Discussionmentioning
confidence: 75%
“…Although controversial, in other studies the Th17 cells did not show encephalitogenicity (Yang et al, 2009;Ghoreschi et al, 2010;Lee et al, 2014). As TGFb is crucial for regulatory T cell (Treg) induction and function (Horwitz et al, 2003) it is unlikely that laquinimod acts through induction of Treg.…”
Section: Discussionmentioning
confidence: 95%